The rise of China under the lenses of Social and Political Sciences: four decades challenging widespread assumptions - Pagán Sánchez, Antonio José (Sociología Histórica, 2022)
Since the implementation of the reform and opening-up policies by Deng Xiaoping in 1978, China has undergone a series of rapid changes that have turned it into a great power with prospects for global leadership. Its rise has not only opened up the possibility that, for the first time in the last two centuries, a non-Western country could once again rise to the top of the international order. The changes in China over the past four decades have also refuted a considerable number of assumptions and arguments held from different angles of the social and political sciences. This paper will analyze how the rise of China has debunked some of the main paradigms and theories in the field of International Relations, democratization, and globalization. The present study concludes that the multidimensional implications of China's rise were not, to a large extent, anticipated by some of the mainstream theories of these disciplines.